1997
DOI: 10.1038/sj.ejcn.1600357
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between maternal nutritional status and infant’s weight and body proportions at birth

Abstract: Objectives: To examine maternal nutritional status and its relationship to infant weight and body proportions. Design: Retrospective study of births from January±December 1990. Setting: University Hospital of the West Indies, Jamaica. Subjects: Records for 2394 live, singleton births, between 200±305 d gestation. Main outcome measures: Birth weight, crown heel length, head circumference, ponderal index, head circumference:length ratio, placental weight, placental:birth weight ratio. Results: Mothers who were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
58
1
5

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 18 publications
10
58
1
5
Order By: Relevance
“…However parity was controlled for in these analyses and was found to have no significant effect on birth size. Women with lower weights in early pregnancy have been described as having smaller babies (Thame et al, 1997). This was not seen in this study as there was no significant difference seen between the birth weights of the infants of these two groups, despite the lower anthropometric measurements of the adolescents in the first trimester.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…However parity was controlled for in these analyses and was found to have no significant effect on birth size. Women with lower weights in early pregnancy have been described as having smaller babies (Thame et al, 1997). This was not seen in this study as there was no significant difference seen between the birth weights of the infants of these two groups, despite the lower anthropometric measurements of the adolescents in the first trimester.…”
Section: Discussioncontrasting
confidence: 43%
“…It has been shown that maternal pre-pregnancy weight and the weight gained during pregnancy influence birth weight (Abrams and Laros, 1986;Scholl et al, 1991;Thame et al, 1997;Abrams et al, 2000). The components of maternal pre-pregnancy weight and weight gained during pregnancy may be associated with or influence birth anthropometry.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that these were representative of the entire cohort as their anthropometry at birth was similar to that reported in studies of Jamaican newborns conducted in the 1970s (Lowry & Bailey, 1978) and 1990s (Thame et al, 1997).…”
Section: Discussionsupporting
confidence: 65%
“…Details related to mother's name, address, antenatal measurements of weight, height, blood pressure, haemoglobin concentration, gestational length, and date of delivery were abstracted from the hospital record. Routinely recorded measurements of birth weight, crown -heel length, crown -rump length and head circumference were also noted (Thame et al, 1997). Children were instructed to fast from 10:00 pm the night before the study and, together with their parent, were brought to the TMRU by 07:00 h.…”
Section: Methodsmentioning
confidence: 99%
“…Birthweight by gestational age can be influenced by race, 3-8 ethnicity within and between races, 4,9-14 socioeconomic status, 15 gestational diabetes, 16 maternal smoking, maternal height and weight, 17 maternal weight gain during pregnancy, 18 and the newborn's sex. [3][4][5] Second-generation immigrants have been shown to have larger birthweight newborns than their first-generation counterparts.…”
Section: Introductionmentioning
confidence: 99%